KEDALIH - Ni Komang Putriana Agustini; Anak Agung Ketut Oka Adnyana; Ni Nyoman Kasih (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2025)
Abstract Kedalih is accusation or slander, Rangdaning Jero Agung was accused of killing her husband and slandered by the local community for having black magic so that Randaning Jero Agung's patience ran out, and she meditated at Pura Dalem Blanjong to ask for supernatural powers. And was given supernatural powers, namely Legu Gondong which made the local community restless because of the plague in the form of Legu (mosquitoes). The meaning of